1989
DOI: 10.1088/0953-4075/22/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the three-photon detachment cross sections of the negative ions of iodine, bromine and fluorine at the wavelength 1.0642 mu m

Abstract: The three-photon detachment cross sections of the ions F-, Br-and Iare measured, using the fundamental 1064.2 nm wavelength of a single-mode Nd:YAG laser. The detachment signal is measured by detecting the neutral atoms produced from an ionic beam of kinetic energy 1.2 keV. The data analysis takes into account the laser pulse time profile, the actual spatial profile of the laser beam in the interaction region, and the fast motion of the ions through the laser beam during the laser pulse. Saturation of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…These results follow immediately from (57) and (58), where only terms with k = 0 contribute for 10 l = 0. Here θ is the angle between n andk.…”
Section: Perturbative Analysis Of Angular Distributions For Ellipticasupporting
confidence: 72%
See 1 more Smart Citation
“…These results follow immediately from (57) and (58), where only terms with k = 0 contribute for 10 l = 0. Here θ is the angle between n andk.…”
Section: Perturbative Analysis Of Angular Distributions For Ellipticasupporting
confidence: 72%
“…Experimental interest in negative ions burgeoned only at the end of the 1980s, when a number of measurements (mostly, for negative halide ions) were performed in the perturbative laser intensity regime: in 1987 Trainham et al [55] measured the two-photon detachment cross section for Cl − , and beginning in 1989, a number of other groups carried out measurements of two-and three-photon cross sections for other ions [56][57][58][59][60]. In 1990, Blondel et al [61] measured the first multiphoton detachment ADs (for two-and three-photon detachment of Br − ).…”
Section: Status Of Multiphoton Detachment Of Negative Ionsmentioning
confidence: 99%
“…The experimental results are shown in figure 2 by open symbols. Blondel et al (1989b) and Kwon et al (1989) However, the best results of the present paper, shown by a solid curve in figure 2, indicate that the cross section is substantially larger. Let us repeat once more that this increase of the cross section is due to the events which happen at large separations, where all correlation corrections are controlled very well.…”
Section: Resultssupporting
confidence: 40%
“…As far as three-photon detachment from negative ions is concerned, the experimental and theoretical results are more scarce than those on the two-photon detachment. Thus, there have been only two experimental measurements of the cross section for F − at a single photon energy performed by Blondel et al (1989b) and Kwon et al (1989), and a few theoretical values obtained in the early calculations by Crance (1987Crance ( , 1988. Recently van der Hart (1996) applied an R-matrix Floquet approach to study the photodetachment from F − and Cl − for n = 1, 2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…This saturation methodology has been also used to evaluate the absolute photo-detachment cross-section of trapped ions [31,32], or into the case of a three-photon set-up [33]. Several mathematical models have been proposed to modelize the saturation effect and to extract r from the measurements, as Cervenan and Isenor [34], considering immobile neutral species interacting with laser beam, or Boulassier [35], considering a gaussian profile interacting homogeneously distributed negative ions, or Blondel et al [33].…”
Section: Introductionmentioning
confidence: 99%